Russia’s Soft Power - Łoś, Robert (Historia i Polityka, 2021)
Russia has always been a country seeking the Great Power status. Even though it lost its importance after the collapse of the Soviet Union, the desire to return to the role of the creator of international order force it to introduce new strategy that will implement soft power resources. This represents a certain obstacle for Russia, which traditionally is accustomed to hard power resources like economic pressure or the use of armed forces. Culture is Russia’s soft power resource that is significant. Values can be more problematic for Russia, because in Moscow’s intentions they should be different from the Western values. Russia is trying to create an alternative soft power project, competitive to that of the West. Russia is trying to make good use of its diplomacy, including digital diplomacy, in order to show the use of its hard power to be seen as soft.